Parallel systems in healthcare: Addressing Indigenous health equity in Canada - Anika Sehgal; Andrea Kennedy; Katharine McGowan; Lynden (Lindsay) Crowshoe (Global Public Health)
The Canadian public healthcare system faces significant challenges in performance. While the formal healthcare system addresses funding, access and policy, there is a critical need to prioritise the informal system of community-oriented networks. This integration aligns with the World Health Organization’s primary health care approach, emphasising a whole-of-society strategy for health equity. Canada’s healthcare, harmonised through the Canada Health Act of 1984, focuses on need over ability to pay. Despite successes, the system struggles with social determinants of health and widening health inequities, especially among Indigenous peoples. Historical policies of forced assimilation have led to poor health outcomes and lower life expectancies for Indigenous populations. The Truth and Reconciliation Commission’s Calls to Action stress removing barriers at multiple levels to improve Indigenous health. Indigenous perspectives on health, emphasising holistic wellness, contrast with Western healthcare’s acute-illness focus. The emergence of parallel systems, informal networks within healthcare, reflects dissatisfaction with traditional approaches. Recognising the parallel system within Indigenous health, as proposed, can transform healthcare to better meet population needs. Systems mapping of Indigenous PHC in Alberta revealed numerous entities providing healthcare access, highlighting the importance of adequately funding and integrating these parallel systems to advance health equity.